2017
DOI: 10.1016/j.amepre.2017.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Flavored Tobacco Product Use in Youth and Adults: Findings From the First Wave of the PATH Study (2013–2014)

Abstract: Introduction The 2009 Family Smoking Prevention and Tobacco Control Act banned characterizing flavors other than menthol in cigarettes, but did not restrict their use in other forms of tobacco (e.g., smokeless, cigars, hookah, e-cigarettes). Methods A cross-sectional analysis of Wave 1 data from 45,971 U.S. adults and youth, aged ≥12 years in the Population Assessment of Tobacco and Health (PATH) Study collected in 2013–2014, was conducted in 2016. This study examined: (1) the prevalence and reasons for use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
213
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(231 citation statements)
references
References 32 publications
(22 reference statements)
10
213
2
1
Order By: Relevance
“…Our results add to the body of literature showing flavored tobacco product use is high appeals to both youth 9,10,1416 and young adults. 16,17 More than 4 out of every 5 past 30-day e-cigarette or tobacco users in our studies from Texas reported using a flavored product.…”
Section: Discussionsupporting
confidence: 68%
“…Our results add to the body of literature showing flavored tobacco product use is high appeals to both youth 9,10,1416 and young adults. 16,17 More than 4 out of every 5 past 30-day e-cigarette or tobacco users in our studies from Texas reported using a flavored product.…”
Section: Discussionsupporting
confidence: 68%
“…Menthol cigarette use is now growing in all groups, but particularly among white and Hispanic young adults,9 and our study demonstrates that flavour capsule products are being disproportionately used by those very groups for whom menthol use is expanding. Studies are needed to understand if the introduction of flavour capsule cigarettes may in part be responsible for the growth in the menthol market.…”
Section: Discussionmentioning
confidence: 70%
“…Here, we expand on the previous consumer marketing panel study9 by examining the characteristics of flavour capsule smokers using data from the nationally representative Population Assessment for Tobacco and Health (PATH) Study 12. We further assess whether smoking histories, measures of nicotine dependence and reasons for product selection differ among flavour capsule cigarette smokers compared with mentholated and non-mentholated cigarette smokers among those with the highest prevalence of flavour capsule use: smokers aged 18–24 years.…”
Section: Introductionmentioning
confidence: 99%
“…Most respondents to a large population survey who report having ever used a tobacco product state that the first product used was ‘flavoured to taste like menthol, mint, clove, spice, candy, fruit, chocolate, alcohol (such as wine or cognac), or other sweets' 8. Furthermore, the prevalence of current tobacco use (that is, smoking/using tobacco products some days or everyday) is significantly higher for those whose first tobacco product was flavoured 8. During 2013–2014, 65.4% of first-time cigar users aged 12–17 years smoked a flavoured cigar, and 71.7% of past 30-day cigar users smoked flavoured cigars 9.…”
Section: Introductionmentioning
confidence: 99%